CORPORATE GOVERNANCE DAN LEVERAGE TERHADAP NILAI PERUSAHAAN DENGAN KUALITAS LABA SEBAGAI VARIABEL MEDIASI - Fondha Mulyo Utomo; Wiwik Dianawati (Jurnal Investasi Islam, 2017)
This study aims to obtain evidence of the influence of good corporate governance as measured by the number of boards of directors, institutional ownership, audit committee, and auditor’s reputation and leverage have an influence on the value of the company through the quality of earnings at manufacturing companies in Indonesia Stock Exchange. The population used in this study is a manufacturing company listed on the Indonesia Stock Exchange in 2013-2016. Sampling technique in this study using simple random sampling, the number of samples 40 companies.The test results show that the number of boards of directors proved to negativelyaffect the value of the company. Institutional ownership and leverage are not proven to affect the value of the company. The auditor’s reputation proved to have a positive effect on the company’s value.The quality of profit is able to mediate the relationship between the number of boards of directors against the value of the company. The quality of profit is not a mediating variable between institutional ownership and the auditor’s reputation of the firm’s value. The quality of profit is able to mediate the relationship between leverage to firm value. The quality of earnings has an influence on the firm value.